Associations Between Cadence and Knee Loading in Patients With Knee Osteoarthritis. Issue 11 (24th September 2021) - Hart, Harvi F.; Birmingham, Trevor B.; Primeau, Codie A.; Pinto, Ryan; Leitch, Kristyn; Giffin, J. Robert
Abstract : Objective: To test the hypothesis that higher walking cadence is associated with lower knee loading, while controlling for walking speed, in patients with medial compartment tibiofemoral osteoarthritis (OA). Methods: A total of 691 patients underwent quantitative gait analysis, including 3‐dimensional knee moments and temporospatial parameters. Using multivariate linear regression, we tested the association of walking cadence with the knee adduction moment angular impulse (a surrogate measure of medial knee compartment load throughout the stance), while controlling for walking speed. We repeated the analysis while also adjusting for sex, age, body mass index, radiographic OA, knee pain, lateral trunk lean, foot progression angle, and mechanical axis angle, and while replacing the knee adduction moment angular impulse with other surrogate measures of knee loading. Results: While controlling for walking speed, we found that a lower cadence was associated with higher knee adduction moment angular impulse (standardized β = –0.396, P < 0.001), suggesting a 0.02% body weight × height × seconds (%BW × Ht × s) decrease in impulse for each step per minute increase in cadence (unstandardized β –0.020 %BW × Ht × s [95% confidence interval –0.027, –0.015]), and remained consistent after adjusting for covariates. A lower cadence was also associated with higher first (standardized β = –0.138, P = 0.010) and second peak knee adduction moment (standardized β = –0.132, P = 0.018), higher peak knee flexion moment (standardized β = –0.128, P = 0.049), and vertical ground reaction force (standardized β = –0.116, P = 0.035) in the adjusted analyses. Conclusion: When controlling for walking speed, we found that a lower cadence is associated with higher knee loading per step in patients with medial tibiofemoral OA. Future research should investigate the potential beneficial biomechanical and clinical effects of increasing walking cadence in patients with knee OA.